Morphological comparison of Delminichthys ghetaldii (Steindachner, 1882), D. adspersus (Heckel, 1843), D. jadovensis (Zupančič & Bogutskaya, 2002) and D. krbavensis (Zupančič & Bogutskaya, 2002), endemic species of the Dinaric karst, Croatia. (8th February 2017) - Mustafić, P.; Buj, I.; Opašić, M.; Zanella, D.; Marčić, Z.; Ćaleta, M.; Šanda, R.; Horvatić, S.; Mrakovčić, M.
Summary: The objectives of this study were to gain a new understanding of the morphology of four endemic Delminichthys species, to determine the presence of morphological differences among populations and species, and to reveal reductive characters that might be connected with underground migrations. Morphometric and meristic characters were measured and statistically compared between populations and species. The study was conducted in the Dinaric region of Croatia and Bosnia and Herzegovina in the year 2013. Interpopulation variability observed for body shape (all size‐independent morphometric characters significantly differed among populations) could be a reflection of the varying ecological conditions, although it might also imply the isolation of populations belonging to the same species. The number of lateral line scales (21–37 in D. krbavensis, 47–63 in D. jadovensis, 52–74 in D. adspersus, 88–105 in D. ghetaldii ) proved to be the best diagnostic character for the Delminichthys species. Nevertheless, differences among the species in the number of pectoral and ventral fin rays, colouration, appearance of the lateral line, position of the mouth and presence of the groove above the upper lip were also observed.